Harnessing ethylene-producing bacteria for fruit bio-ripening: a comprehensive review - Brunda, Y; Muthuvel, I; Kavitha, PS; Karthikeyan, M; Ramesh, D (Plant Science Today, 2024)
Fruit ripening is a complex biological process regulated by various endogenous and exogenous factors, with ethylene playing a pivotal role as a gaseous hormone. Traditionally, ethylene for commercial use has been derived from environmentally hazardous processes. However, the discovery of ethylene-producing bacteria presents a sustainable alternative for fruit ripening. This review explores the mechanisms and potential of utilizing ethylene-producing bacteria in the bio-ripening of fruits. Through an analysis of current research, we elucidate the synthesis pathways of ethylene in microorganisms, optimization techniques to enhance ethylene production, and the compatibility among microbial strains for the development of effective microbial consortia. Recent studies have demonstrated the efficacy of ethylene-producing bacteria, such as Bacillus and Pseudomonas species, in bio-ripening fruits like kiwifruit, plums, bananas, and apples. The optimization of growth conditions and the development of microbial consortia aim to maximize ethylene production efficiency While minimizing environmental impacts. This review underscores the importance of ethylene-producing bacteria in revolutionizing fruit ripening technology and advancing sustainable agricultural practices. By providing insights into the opportunities and challenges associated with bio-ripening fruits by ethylene-producing bacteria, this review seeks to guide future research and innovation in the field. Ultimately, using ethylene-producing bacteria offers a promising avenue for achieving safe, environmentally friendly, and efficient fruit ripening methods in agricultural practices.